ARNALDO ALCUBILLA, Enrique; DELGADO-IRIBARREN GARCÍA-CAMPERO, Manuel y SÁNCHEZ NAVARRO, Ángel J. (2013): Iniciativa legislativa popular. Madrid: La Ley (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
ARNALDO ALCUBILLA, Enrique; DELGADO-IRIBARREN GARCÍA-CAMPERO, Manuel y SÁNCHEZ NAVARRO, Ángel J. (2013):Iniciativa legislativa popular. Madrid: La Ley.